Impact of land use and land cover change on the landscape pattern and service value of the village ecosystem in the karst desertification control - Wang, Qi; Xiong, Kangning; Zhou, Jiayi; Xiao, Hua; Song, Shanhai (Frontiers in Environmental Science, 2023)
The study of village-scale landscape patterns and ecosystem services (ES) based on land use and land cover (LULC) is significant in promoting the sustainable development of village ecosystems. Based on the GF-2 image, this study selected the village ecosystems of karst plateau mountains which are controlled by potential mild rocky desertification control (RDC), and the period of 2015-2020 for the karst rocky desertification control (KRDC) was chosen as the study period. The spatial and temporal changes in landscape pattern index and ecosystem service values (ESV) under land use and land cover change (LULCC) are analyzed using the land use matrix, landscape pattern index, and topographic position index (TPI), and equivalence method. The results show that: (1) forest land, orchard land, and construction land increase, and dryland and grassland decrease. The landscape shows an aggregated state, with spreading and connectivity increasing while fragrant diversity is decreasing. (2) The total ESV increased by CNY 63.45×104, with regulating and cultural services on the rise and supply and support services on the decline. (3) With the rise of the TPI, the value of the supply services is inversely U-shaped, while the value of the remaining services increases. This study provides a case study about karst rocky desertification areas for village-scale ecosystem services research.